2011
DOI: 10.12659/msm.881977
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of cardiac hepatopathy in patients with right heart failure

Abstract: SummaryBackgroundSome patients with right heart failure develop cardiac hepatopathy (CH). The pathophysiology of CH is thought to be secondary to hepatic venous congestion and arterial ischemia. We sought to define the clinical and hemodynamic characteristics associated with CH.Material/MethodsA retrospective cross sectional analysis was performed in which subjects were identified from our institutional cardiology database if echocardiography showed either right ventricular (RV) hypokinesis or dilatation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 17 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…In patients with severe heart failure, particularly right heart failure, hepatic injury results from chronic congestion, with or without superimposed decline in hepatic arterial perfusion. 6 Although this pathologic entity has been well known for decades, there has been no useful grading system for prospective and comparative studies, resulting in a lack of consistent reporting parameters for liver histopathology that potentially hinders the communication of appropriate information to the clinicians. In this study, we have proposed a simple scoring system-the congestive hepatic fibrosis score-and have demonstrated that this score correlates well with echocardiography-derived right atrial pressure as well as both right atrial and right ventricular dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe heart failure, particularly right heart failure, hepatic injury results from chronic congestion, with or without superimposed decline in hepatic arterial perfusion. 6 Although this pathologic entity has been well known for decades, there has been no useful grading system for prospective and comparative studies, resulting in a lack of consistent reporting parameters for liver histopathology that potentially hinders the communication of appropriate information to the clinicians. In this study, we have proposed a simple scoring system-the congestive hepatic fibrosis score-and have demonstrated that this score correlates well with echocardiography-derived right atrial pressure as well as both right atrial and right ventricular dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…As RV dysfunction progresses to overt RV failure, the RV chamber becomes more spherical and tricuspid regurgitation is aggravated, leading to progressive venous congestion . Venous congestion and increased central venous pressure also lead to impairment of renal, intestinal, and hepatic function, which are important predictors of poor prognosis in patients with acute RV failure …”
Section: Pathophysiologymentioning
confidence: 99%
“…CH is associated with increased morbidity and mortality in patients with cardiac dysfunction. Previous studies have shown that the most noticeable hemodynamic features are elevated RV, right atrial and hepatic venous pressures in patients with CH 6,7 . Only aminotransferase levels correlate with right heart failure, particularly in patients with acute cardiac dysfunction 6 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that the most noticeable hemodynamic features are elevated RV, right atrial and hepatic venous pressures in patients with CH. 6,7 Only aminotransferase levels correlate with right heart failure, particularly in patients with acute cardiac dysfunction. 6 In contrast, Van Deursen et al found that all abnormal liver function tests were related to high central venous pressure (CVP) but that higher CVP is mainly related to g-GTP and DB, whereas AST, ALT, and TB are associated with low cardiac index.…”
Section: Discussionmentioning
confidence: 99%